Antagonism in Daily Life: An Exploratory Ecological Momentary Assessment Study. (January 2022) - Vize, Colin E.; Ringwald, Whitney R.; Edershile, Elizabeth A.; Wright, Aidan G. C.
Interpersonal antagonism is one of the major domains of maladaptive personality. Structure-based investigations of antagonism have generally been consistent in highlighting the more specific antagonistic traits (e.g., manipulativeness, callousness) that underlie the broader domain. However, less work has attempted to merge structural and functional accounts of antagonism to assess how specific antagonistic traits manifest in daily life. This exploratory study examined how antagonism and its specific features relate to outcomes assessed using ecological momentary assessment (EMA) methods. Across four independent EMA samples ( N range = 297–396; total N = 1, 365; observations per outcome = 5, 419–17, 735), we investigated how antagonistic traits related to theoretically relevant, EMA-based outcomes (e.g., affect, empathy, coldness-warmth in interpersonal interactions). Results showed robust findings across samples and operationalizations of antagonism (e.g., antagonism's relation with negative affect), along with more mixed results (e.g., antagonism's RELATION with different measures of empathy). We discuss future research directions for structural and functional accounts of antagonism.